1975
DOI: 10.1007/bf01906386
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of local blood flow with heat clearance

Abstract: Measurements of the local blood flow through organs by means of heated thermistor-probes enable one to perform continuous recordings of flow. The principle is based on the measurement between a heated and an unheated probe, both implanted in the tissue or placed on the superficial layer of the organ. The flow-measure for this type of blood flow recording is the heat transported from the heated site of the tissue. It is measured in cal-cm(-1)-sec(-1)-degree C(-1). This is the dimension of the heat conductance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…(1975) and Swank et al (1978) injected cold blood into the left atrium and measured the heat change in a local area of the myocardium following injection. The same principle has been applied in the dog kidney in which thermal conductivity was measured after heating a small adjacent area (Muller-Schauenburg et al 1975;Olshausen et al 1976). Similarly, the principle of heat clearance has recently been applied to quantitative measurement of regional tissue blood flow in the myocardium (Hernandez et a!.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1975) and Swank et al (1978) injected cold blood into the left atrium and measured the heat change in a local area of the myocardium following injection. The same principle has been applied in the dog kidney in which thermal conductivity was measured after heating a small adjacent area (Muller-Schauenburg et al 1975;Olshausen et al 1976). Similarly, the principle of heat clearance has recently been applied to quantitative measurement of regional tissue blood flow in the myocardium (Hernandez et a!.…”
Section: Discussionmentioning
confidence: 99%
“…0144-8757/81/1020-1823 $07.50 ©) 1981 The Physiological Society Local tissue blood supply can be evaluated experimentally as a function of heat transfer or dilution as measured locally by thermistors (Hernandez, Hoffman, Fabian, Siegel & Eherhart, 1979;Muller-Schauenburg, Apfel, Benzing & Betz, 1975;Olshausen, Gross & Kirchein, 1976; Reuben, Singh, Tector, Kampine, Flemma & Lepley, 1975;Shitzer & Eberhart, 1979;Swank, Singh, Flemma, Mullen & Lepley, 1978). In the present communication we describe the application of such a technique for measuring local coronary blood flow using small thermistors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop a simpler and less expensive device to monitor blood flow volume. Thermal methods that measure the peripheral blood flow volume according to skin temperature have been proposed [12][13][14][15][16][17]. However, most of these methods require an external heat source, which increases test time (up to a few minutes) and may harm the subject.…”
Section: Introductionmentioning
confidence: 99%
“…10 Calibration of this probe was carried out with '"Xenon clearance curves which demonstrated a linear relationship between the radioactive diffusion-washout rCBF and thermal diffusion local CBF measurements. These investigators believed that the Peltier flow probe was preferable to the heat clearance methods proposed by Betz and associates because it could quantitatively record continuous changes in CBF with reproducible re- 11 These investigators demonstrated that such a system could measure the thermal conductivity of tissue in the vicinity of a small heated thermistor maintained at a fixed temperature difference above a reference thermistor. The power consumption of the heated thermistor is proportional to the thermal conductivity of the tissue which is directly related to local blood flow.…”
mentioning
confidence: 99%